Differential Association of HIV Funding With HIV Mortality by Race/Ethnicity, United States, 1999-2017. (July 2020) - Truman, Benedict I.; Moonesinghe, Ramal; Brown, Yolanda T.; Chang, Man-Huei; Mermin, Jonathan H.; Dean, Hazel D.
Objective: Federal funds have been spent to reduce the disproportionate effects of HIV/AIDS on racial/ethnic minority groups in the United States. We investigated the association between federal domestic HIV funding and age-adjusted HIV death rates by race/ethnicity in the United States during 1999-2017. Methods: We analyzed HIV funding data from the Kaiser Family Foundation by federal fiscal year (FFY) and US age-adjusted death rates (AADRs) by race/ethnicity (Hispanic, non-Hispanic white, non-Hispanic black, and Asian/Pacific Islander and American Indian/Alaska Native [API+AI/AN]) from Centers for Disease Control and Prevention WONDER detailed mortality files. We fit joinpoint regression models to estimate the annual percentage change (APC), average APC, and changes in AADRs per billion US dollars in HIV funding, with 95% confidence intervals (CIs). For 19 data points, the number of joinpoints ranged from 0 to 4 on the basis of rules set by the program or by the user. A Monte Carlo permutation test indicated significant ( P < .05) changes at joinpoints, and 2-sided t tests indicated significant APCs in AADRs. Results: Domestic HIV funding increased from $10.7 billion in FFY 1999 to $26.3 billion in FFY 2017, but AADRs decreased at different rates for each racial/ethnic group. The average rate of change in AADR per US billion dollars was −9.4% (95% CI, −10.9% to −7.8%) for Hispanic residents, −7.8% (95% CI, −9.0% to −6.6%) for non-Hispanic black residents, −6.7% (95% CI, −9.3% to −4.0%) for non-Hispanic white residents, and −5.2% (95% CI, −7.8% to −2.5%) for non-Hispanic API+AI/AN residents. Conclusions: Increased domestic HIV funding was associated with faster decreases in age-adjusted HIV death rates for Hispanic and non-Hispanic black residents than for residents in other racial/ethnic groups. Increasing US HIV funding could be associated with decreasing future racial/ethnic disparities in the rate of HIV-related deaths.